Medieval Bruges, c. 850-1550 - Brown, Andrew 1964-; Dumolyn, Jan 1974-; Cambridge University Press (Cambridge University Press, 2018)
Origins and early history -- The urban landscape I: c. 1100 - c. 1275 -- Production, markets and socio-economic structures I: c. 1100 - c. 1320 -- Social groups, political power and institutions, I: c. 1100 - 1304 -- The urban landscape II: c. 1275 - c. 1500 -- Production, markets and socio-economic structures II: c. 1320 - c. 1500 -- Political power and social groups, c. 1300 - c. 1500 -- Religious practices c.1200-1500 -- Texts, images and sounds in the urban environment, c. 1100 - c. 1500 -- Bruges in the sixteenth century: a "return to normalcy" -- Conclusion: Bruges within the medieval urban landscape